2021
DOI: 10.1007/s00264-021-05214-y
|View full text |Cite
|
Sign up to set email alerts
|

Candida periprosthetic joint infections — risk factors and outcome between albicans and non-albicans strains

Abstract: Background Despite its scarcity, fungal periprosthetic joint infection (PJI) is of great clinical relevance as diagnosis and treatment are highly challenging. Previous analyses focused on the treatment rather than the role of the causative fungal agent on clinical outcome. This is the largest study of its kind to evaluate Candida strain–dependent differences in patients with fungal PJI. Methods We retrospectively analyzed 29 patients who underwent surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…However, the two-stage protocol was statistically more effective for Candida parapsilosis PJI in comparison to the one-stage protocol ( p = 0.02) and in comparison to the two-stage treatment results of Candida albicans ( p = 0.4). Similar results were received by Karczewski et al, who compared albicans and non-albicans strains causing PJIs [ 24 ]. They reported an 80% of success rate for the non-albicans and 56.3% for albicans PJIs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, the two-stage protocol was statistically more effective for Candida parapsilosis PJI in comparison to the one-stage protocol ( p = 0.02) and in comparison to the two-stage treatment results of Candida albicans ( p = 0.4). Similar results were received by Karczewski et al, who compared albicans and non-albicans strains causing PJIs [ 24 ]. They reported an 80% of success rate for the non-albicans and 56.3% for albicans PJIs.…”
Section: Discussionsupporting
confidence: 85%
“…A total of 12 studies comprising 153 cases of Candida PJI were included in the final analysis ( Table 2 ) [ 12 , 21 , 22 , 23 , 24 , 25 , 26 , 32 , 33 , 34 , 35 , 36 ]. The number of hip-to-knee PJI was 86 (54.8%) to 67 (46.2%), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found prosthesis failure rates after revision arthroplasty to be significantly elevated in patients with rheumatoid arthritis, further stressing the need for a more personalized diagnostic and therapeutic approach in these patients. Similarly, prosthesis survival rates after revision arthroplasty have been found to be significantly decreased in non-rheumatoid arthritis patients [ 11 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infections of implants are rare events, but their treatment involves more medical problems and aggressive surgical treatments than normal bacterial infections. Most fungal infections are caused by candida species, such as Candida albicans and Candida parapsilosis [28,29].…”
Section: Common Microorganisms Infecting Implantsmentioning
confidence: 99%